Assay for screening for six antimalarial drugs and one metabolite using dried blood spot sampling, sequential extraction and ion-trap detection. (November 2010) - Blessborn, Daniel; Romsing, Susanne; Bergqvist, Yngve; Lindegardh, Niklas
Background: More parasites are becoming resistant to antimalarial drugs, and in many areas a change in first-line drug treatment is necessary. The aim of the developed assay is to help determine drug use in these areas and also to be a complement to interviewing patients, which will increase reliability of surveys.Results: This assay detects quinine, mefloquine, sulfadoxine, pyrimethamine, lumefantrine, chloroquine and its metabolite desethylchloroquine in a 100-µl dried blood spot. Most of the drugs also have long half-lives that make them detectable at least 7 days after administration. The drugs are extracted from the dried blood spot with sequential extraction (due to the big differences in physicochemical properties), solid-phase extraction is used as sample clean-up and separation is performed with gradient-LC with MS ion-trap detection.Conclusion: Detection limits (S/N > 5:1) at 50 ng/ml or better were achieved for all drugs except lumefantrine (200 ng/ml), and thus can be used to determine patient compliance. A major advantage of using the ion-trap MS it that it will be possible to go back into the data and look for other drugs as needed.